2021
DOI: 10.1186/s12935-021-02231-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a pyroptosis-related prognostic signature for thyroid cancer

Abstract: Background Pyroptosis is a form of programmed cell death triggered by inflammasomes. However, the roles of pyroptosis-related genes in thyroid cancer (THCA) remain still unclear. Objective This study aimed to construct a pyroptosis-related signature that could effectively predict THCA prognosis and survival. Methods A LASSO Cox regression analysis was performed to build a prognostic model based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…In HCC, a recent study revealed a mechanism of action for sorafenib, eliciting macrophage pyroptosis that enhances NK-cell effector function and ultimately effective HCC cell killing [ 10 ]. Prognostic signatures based on PRGs were established for lung adenocarcinoma, ovarian cancer, and thyroid cancer [ 11 13 ]. However, the prognostic value of PRGs in HCC has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…In HCC, a recent study revealed a mechanism of action for sorafenib, eliciting macrophage pyroptosis that enhances NK-cell effector function and ultimately effective HCC cell killing [ 10 ]. Prognostic signatures based on PRGs were established for lung adenocarcinoma, ovarian cancer, and thyroid cancer [ 11 13 ]. However, the prognostic value of PRGs in HCC has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has several advantages over previous studies on certain cancers. First, previous studies focused on the development and validation of prognostic models involving certain cancer types [32][33][34][35]. Our studies aimed to assess pyroptosis levels in cancer as a whole, and our model of pyroptosis levels is thus more universal.…”
Section: Discussionmentioning
confidence: 99%
“…The model was determined by penalty parameter (λ) with ten-fold cross-validation following the minimum criteria. The risk score of each THCA patient was calculated by the following formula: Risk score = βA * Expression level of Gene A + βB * Expression level of Gene B + … + βN * Expression level of Gene N, (β: regression coe cient) 24 . Patients were separated into high-and low-risk group based on the median risk score.…”
Section: Construction and Validation Of The Immune-related Ernas Prog...mentioning
confidence: 99%